Risk Assessment of Trace Element Contamination in Drinking Water and Agricultural Soil: A Study in Selected Chronic Kidney Disease of Unknown Etiology (CKDu) Endemic Areas in Sri Lanka - W. P. R. T. Perera; M. D. N. R. Dayananda; D. M. U. C. Dissanayake; R. A. S. D. Rathnasekara; W. S. M. Botheju; J. A. Liyanage; S. K. Weragoda; K. A. M. Kularathne (Journal of Chemistry)
Unexplained or unclear etiology of chronic kidney disease (CKDu) has been reported in Sri Lanka’s North Central Province (NCP) for more than two decades. Meanwhile, high exposure to heavy metals/metalloids and their accumulation are recognized as the origin of many acute and chronic diseases in certain vulnerable human tissues including kidneys. This study evaluates the contamination status of heavy metals/metalloids of the drinking water and agricultural soil in two CKDu endemic areas compared with a reference area in Sri Lanka based on common indexes and attribute of the commonly used fertilizers evaluated to identify the basic sources of toxic metals in the agricultural soil. Mean concentrations of heavy metals/metalloids such as Mn, Co, As, Cd, Pb, Cu, Zn, and Fe in drinking water of CKDu endemic areas were far below Sri Lankan water quality standards (permissible limits). In addition, all sampling locations dropped below the medium range of the heavy metal pollution index of water (HPI 15–40). Geoaccumulation indexes (Igeo) of soil reveal that paddy soil in CKDu endemic areas is being moderately polluted with toxic metals/metalloids such as As, Pb, Cu, Ni, Cr, Zn, and Cd. On the other hand, the application of fertilizers, which contained a high dose of toxic metals, could be the driving force for agricultural soil pollution, and limitless application of low-quality fertilizer would lead to more soil contamination with heavy metals. Hence, hazardous metals can be incorporated into the food chains via contaminated paddy soil.